Familial pancreatic adenocarcinoma: A retrospective analysis of germline genetic testing in a French multicentre cohort. Issue 6 (3rd September 2019) - Schwartz, Mathias; Korenbaum, Clement; Benfoda, Meriem; Mary, Mickael; Colas, Chrystelle; Coulet, Florence; Parrin, Melissa; Jonveaux, Philippe; Ingster, Olivier; Granier, Sandra; De Mestier, Louis; Cros, Jerome; et al.
Abstract: The rate of genetic diagnosis of French patients with familial pancreatic ductal adenocarcinoma (PDAC) is not known. We report germline genetic testing data from 133 index cases meeting criteria for familial pancreatic cancer (FPC) as well as 87 'FPC‐like' index cases who did not fulfilled strict FPC definition but were evocative for a PDAC predisposition. The overall rate of genetic diagnosis (in BRCA1, BRCA2, CDKN2A, and ATM genes) was 8.3% in FPC patients and 4.6% in FPC‐like patients, consistent with the literature in other populations. Genetic variants were also identified in FANCA and BAP1 genes, as well as in the CDKN2A p12 transcript. This pancreas‐specific transcript is a known key player in driving pancreatic oncogenesis. This might be the first described case of a PDAC genetic predisposition due to a variant in this specific transcript. Abstract :